Biomechanical evaluation of custom-made short implants with wing retention applied in severe atrophic maxillary posterior region restoration: A three-dimensional finite element analysis - Yang, Zhen; Zhang, Jingran; Xu, Zexian; Liu, Xiaoqiang; Yang, Jianjun; Tan, Jianguo (Frontiers in Bioengineering and Biotechnology, 2023)
Severe bone atrophy in maxillary posterior region poses a big challenge to implant restoration. The digital designed and customized short implant with wing retention provides a safer and minimal invasive implant restoration scheme in such circumstances. The small titanium wings are integrated with the short implant supporting the prosthesis. Using digital designing and processing technology, the wings fixed by titanium screws can be flexible designed, providing the main fixation. The designation of wings will influence the stress distribution and the implant stability. This study analyzes the position, structure, and spread area of the wings fixture scientifically by means of three-dimensional finite element analysis. The designation of wings is set to linear, triangular, and planar styles. Under the simulated vertical and oblique occlusal forces, the implant displacement and stress between the implant and the bone surface are analyzed at different bone height of 1mm, 2mm, and 3mm. The finite element results show that the planar wing designation can better disperse the stress. By adjusting the cusp slope to reduce the influence of lateral force, the short implant with planar wing fixture can be used safely even the residual bone height is only 1mm. The results of the study provide a scientific basis for the clinical application of this new customized implant.